ANALISIS PENGARUH KEPUASAN, MOTIVASI, DAN STRES KERJA TERHADAP KINERJA TENAGA PARAMEDIS KEPERAWATAN DI RSUD KABUPATEN MOROWALI - Latiho, Rahmawati S. (Katalogis, 2016)
Paramedics have important roles in providing health care to the community. Some factors affecting the performance of paramedics in providing good services, among others, are satisfaction, motivation, and stress in the workplace. This research intends to determine the influence of satisfaction, motivation, and work strees on paramedics’ performance in The regional hospital of Morowali. Population of this study consists of 213 paramedics and the 68 samples selected aare paramedics with the status of civil servants and contracts. The data is collected through questionnaires and analyzed with multiple regressions analysis. The results of the test show that: 1) satisfaction, motivation, and work stress simultaneously have significant influence on paramedics’ performance with adjusted R² value of 0,111 on sig 0,015; 2) satisfaction variables has positive and significant influence on paramedics’ performance with coefficient regresion value of 0,095 an sig 0,050; 3) motivation has positive but insignificant influence on paramedics’ performance with coeficient regression value of 0,095 on sig 0,468; 4) stress has negative and insignification influence on paramedics’ performance with coefficient regression value of -0,023 on sig 0,648